Effects of steroids on thrombogenic markers in patients undergoing unilateral total knee arthroplasty: A prospective, double‐blind, randomized controlled trial. Issue 3 (6th January 2015) - McLawhorn, Alexander S.; Beathe, Jonathan; YaDeau, Jacques; Buschiazzo, Valeria; Purdue, P. Edward; Ma, Yan; Sculco, Thomas P.; Jules‐Elysée, Kethy
Abstract Venous thromboembolism (VTE) remains an important complication after total knee arthroplasty (TKA). Systemic thrombin generation starts perioperatively. Inflammation, characterized by a rise in interleukin‐6 (IL6), initiates the coagulation cascade, but low‐dose steroids can reduce post‐TKA IL6 levels. This double‐blinded, randomized, placebo‐controlled study enrolled 30 patients undergoing unilateral TKA to assess the effect of perioperative steroids on serum prothrombin fragment (PF1.2), a marker of thrombin generation, and plasmin‐alpha‐2‐antiplasmin complex (PAP), a marker of fibrinolysis. Study patients received 100 mg of intravenous hydrocortisone 2 h prior to surgery, and controls received normal saline. Blood samples, drawn pre‐incision and at 4 h post tourniquet release, were assayed for PF1.2 and PAP. The study group had significantly lower mean PF1.2 at 4 h compared to controls (616 ± 358 pMol/L vs. 936 ± 332 pMol/L, p = 0.037). The mean rise in PF1.2 in the control group was significantly greater compared to the study group (672 ± 173 pMol/L vs. 350 ± 211 pMol/L, p < 0.001). Mean PAP was higher in the study group at 4 h (1639 ± 823 µg/L vs. 1087 ± 536 µg/L), but did not reach statistical significance (p = 0.07). These results may have clinical implications in terms of postoperative VTE risk and management. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???–???, 2015.